Baroque metamorphosis - Lázaro Carreter, Fernando (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
Baroque art, as is well known, tends towards the spectacular and hyperbole, counterbalanced in many cases by a certain ironic naturalism. It was in relation to the former tendency that Ovid truly carne into his own, to the point that the Baroque period has been defined as the true ’aetas ovidiana’. Ovid furnished both plastic artists and writers with mythological sources of inspiration. The trace of such themes is patent in Spanish writers, who at times treat them with the greatest pomp but at others to the detriment of their prestige. And this is invariably done through the transformations learnt in Ovid, transformations that reflect the intellectual instability of the epoque. Some writers are exponents of the conceit as the basic stylistic unit, following the example of the great Latin lyric: one stanza from the Fábula de Píramo y Tisbe would be enough to show this. It is the use of the conceit, as defined by Gracián, that corroborates the inseparability of Conceptism (Conceptismo) and Gongorism (Culteranismo): both artistic forms use this procedure in their transforming technique.